TVET–Sustainable goals linkage: Inclusive education for a sustainable development - Adediran, Ibraheem Adedayo; Ishola, Ajibola Abdulrahamon (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
Technical, Vocational, Education and Training spans our educational systems, from toys for infants to sending children to school to learn Science, Engineering, and Technology. An inclusive society needs real-world education. Equal access for balanced empowerment may be achieved via two techniques. TVET and SDGs work if done well. TVET-SDGs Linkage is a major problem that must be addressed if Nigeria is to fulfil its UN duties, especially in building an inclusive society as outlined in Objectives 4, 5, 8, 10 and 16 of the 17-Point Agenda of the Sustainable Development Goals with 169 goals. Inclusive education promotes a just and equitable society as envisioned by the UN through mobilising stakeholders. The article discusses leveraging TVET to meet Nigeria's SDGs via inclusive education. Secondary schools, vocational centres, technical colleges, polytechnics, and universities must have high-quality teaching and training facilities and highly-trained teaching staff.